The Relationship Between Physical Condition and Medal Achievement of Tarung Derajat Athletes in Bandung Regency at POPDA XIV West Java - Andyka Agyas Pratista; Iman Imanudin; Widy Dewi Nuryanti (Universitas Negeri Semarang, 2026)
Physical condition is a determining factor that determines an athlete's ability to maintain peak performance and technical mastery under competitive pressure. This study aims to analyze the contribution and relationship between physical condition and the medal achievements of Tarung Derajat athletes from Bandung Regency at the 2025 West Java Provincial Student Sport Week (POPDA) XIV event. The research method used is quantitative descriptive with a correlational design and a one-shot case study approach. The research subjects involved 26 athletes (14 male and 12 female) selected using the total sampling technique. The test instruments included flexibility, speed, agility, strength, and endurance, while performance data was converted into numerical scores based on medal achievements. The Shapiro-Wilk normality test showed that the performance data was not normally distributed, so hypothesis testing used Spearman's correlation. The Spearment’s correlation test confirmed a very strong and statistically significant positive relationship between total physical condition and medal achievement with a correlation coefficient of (rs= 0.927; ρ = 0.001) because, this finding empirically proves that physical condition quality is a determining factor that is directly proportional to the chances of winning medals, where the better the athlete’s physical condition, the greater the athlete’s chances of achieving maximum performance.